EFEKTIVITAS MODEL PEMBELAJARAN COOPERATIF LEARNINGTIPE STAD DALAM MENINGKATKAN KEMAMPUAN MENGANALISIS UNSUR INTRINSIK CERPEN “DAERAH GARONG” KARYA M. SHOIM ANWAR OLEH SISWA KELAS XI SMA NEGERI 1 SIBOLGA TAHUN PEMBELAJARAN 2010/2011 - DAHRIANSYAH SITUMEANG (Fakultas Bahasa dan Seni, 2012)
This study aims to determine which is most significant and influential efektiifbetween learning models Learning Cooperatif STAD type of learning modelLearning Completed the ability to analyze the intrinsic elements of short stories.The effectiveness of this model can be seen from the differences in learningoutcomes / elements of the intrinsic ability to analyze short stories in Class XIscience students SMA Negeri 1 Sibolga Learning Year 2010/2011. The studypopulation was all students in grade XI IPA SMA Negeri 1 Sibolga Learning Year2010/2011 which amounted to 170 people. Samples taken in this research clusteras many as 68 people randomly from the population.